Analyzing Motivational Determinants of Shopping Addiction Tendency - ARSLAN, FATMA MÜGE (EGE UNIV, FAC ECONOMICS & ADMIN SCIENCES, 2019)
Shopping addiction tendency is defined as being so occupied about shopping that consumers become driven by uncontrollable shopping urges and as a result of facing negative psychological, social and financial consequences. Based on a field study on university students (N=372), this paper examines hedonic shopping, escapism and negative mood reduction, as motivational determinants of shopping addiction tendency, which is a relatively less studied area of consumer behavior in Turkey. The findings indicate that, hedonic shopping, escapism and negative mood reduction all have significant effect on shopping addiction. Getting its mainstream studies from compulsive buying literature, shopping addiction literature focuses mainly on the enjoyment gathered from shopping action However this study provides new insights into potential antecedents of shopping addiction as negativity avoidance and escapism, which are negative psychological states with respect to shopping addicts quest for shopping enjoyment.
Keywords: Shopping Addiction Tendency; Hedonic Shopping; Negative Mood Reduction; Escapism; BEHAVIORAL ADDICTIONS; CONSUMPTION; ANTECEDENTS; VALIDITY; DISORDER